Organizational Strategies for Strengthening AI-Integrated Ubiquitous Learning in Elementary Schools - Ferdyawati, Dina; Raharja, Setya (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
The rapid advancement of Artificial Intelligence (AI) has accelerated the transformation of elementary education toward ubiquitous learning, requiring schools to establish organizational strategies that effectively support technology-integrated teaching and learning. This study aims to analyze how organizational strategies strengthen AI-integrated ubiquitous learning in elementary schools by emphasizing the alignment between school leadership, teacher capacity, curriculum integration, and digital learning environments. A qualitative case study approach was employed involving selected elementary schools with varying levels of AI implementation. Data were collected through in-depth interviews with school principals, teachers, and educational technology coordinators, complemented by classroom observations of AI-supported instructional practices. The findings indicate that successful AI integration extends beyond technological availability and depends on coherent organizational strategies that foster instructional innovation. Strategic planning, visionary leadership, continuous professional development, curriculum alignment, and adequate digital infrastructure collectively enhance teachers' digital pedagogical competence and facilitate personalized, flexible, and adaptive learning experiences. Furthermore, collaborative school cultures, effective internal communication, and parental engagement reinforce the sustainability of AI-supported instructional practices. These organizational dimensions create enabling conditions for implementing ubiquitous learning by promoting data-informed instruction, increasing student engagement, and supporting continuous improvement in teaching practices. The study concludes that organizational strategies function as critical enablers of AI-integrated pedagogy rather than merely administrative mechanisms, providing a practical framework for elementary schools seeking to implement sustainable, technology-enhanced learning ecosystems that respond to the evolving demands of twenty-first-century education.